2016
DOI: 10.5812/hepatmon.40492
|View full text |Cite
|
Sign up to set email alerts
|

Serological Patterns and Molecular Characterization of Occult Hepatitis B Virus Infection among Blood Donors

Abstract: BackgroundHepatitis B infections, characterized by the presence of a viral genome without detectable hepatitis B surface antigen (HBsAg; Occult hepatitis B infection [OBI]), have been reported recently.ObjectivesWe performed serological and molecular characterization of OBI among blood donors at Jiangsu province blood center during years 2013 and 2014.MethodsAll donor samples were routinely screened by double enzyme-linked immunosorbent assay (ELISA) for hepatitis C virus (HCV), hepatitis B virus (HBV), human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Among the 1,261 blood donors initially screened as HBsAg-/HBV DNA+ in 29 blood centres across China, 918 donors (72.8%) were confirmed as OBI carriers. These OBI donors shared similar male dominance, normal ALT levels, low viral loads, and ages of ≥40 years compared to OBI blood donors from Northern and Eastern Central China and other Asian countries (Table 1) [7,21,22]. HBV genotype C appeared to be slightly over-represented among OBI donors compared to the randomly selected HBsAg+ donor group as suggested by others [8,21–23].…”
Section: Discussionsupporting
confidence: 66%
“…Among the 1,261 blood donors initially screened as HBsAg-/HBV DNA+ in 29 blood centres across China, 918 donors (72.8%) were confirmed as OBI carriers. These OBI donors shared similar male dominance, normal ALT levels, low viral loads, and ages of ≥40 years compared to OBI blood donors from Northern and Eastern Central China and other Asian countries (Table 1) [7,21,22]. HBV genotype C appeared to be slightly over-represented among OBI donors compared to the randomly selected HBsAg+ donor group as suggested by others [8,21–23].…”
Section: Discussionsupporting
confidence: 66%
“…All their OBI isolates were males and mostly below 36 years. This also conforms to the reports of Zheng et al [24] which revealed the male to female ratio of OBI as 3 The result of Alanine Aminotransferase (ALT) from this study showed that all OBI blood donors as well as HBV seronegative samples had normal serum ALT concentration This result correlates with the finding of Lin et al [28]. This corroborates with another report from Chinese blood donors with OBI, which reported normal ALT values from their subjects [23].…”
Section: Occultsupporting
confidence: 92%
“…It has been reported that the substitution of amino acid 145 is the most frequent mutation in this region . Moreover, amino acid changes at 124,125,126, 127, 129, 130,131,133, 136,137, 138,139, 140, 141, 142,144,145,146 and 147 sites have been described in OBI samples . In the present study, 51 of 80 objects (63.75%) contained the “a” determinant mutation.…”
Section: Discussionsupporting
confidence: 54%